1998
DOI: 10.1007/s11661-998-0168-0
|View full text |Cite
|
Sign up to set email alerts
|

In-situ nuclear magnetic resonance investigation of strain, temperature, and strain-rate variations of deformation-induced vacancy concentration in aluminum

Abstract: Critical strain to serrated flow in solid solution alloys exhibiting dynamic strain aging (DSA) or Portevin-LeChatelier effect is due to the strain-induced vacancy production. Nuclear magnetic resonance (NMR) techniques can be used to monitor in situ the dynamical behavior of point and line defects in materials during deformation, and these techniques are nondestructive and noninvasive. The new CUT-sequence pulse method allowed an accurate evaluation of the strain-enhanced vacancy diffusion and, thus, the exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…High strain rates are expected to expedite diffusion of migrating species [24,28,29]. Diffusion may also be enhanced by deformation-induced ''mechanical interdiffusion'' [45].…”
Section: Superimposed Effect Of Deformation On Diffusionmentioning
confidence: 99%
See 1 more Smart Citation
“…High strain rates are expected to expedite diffusion of migrating species [24,28,29]. Diffusion may also be enhanced by deformation-induced ''mechanical interdiffusion'' [45].…”
Section: Superimposed Effect Of Deformation On Diffusionmentioning
confidence: 99%
“…jog dragging and dipole annihilation [26,27]. As such, the mobile vacancy concentration will be proportional to both the imposed strain rate and the dislocation density [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Now the question remains whether such a vacancy concentration can be reached during the bonding process. In situ nuclear magnetic resonance (NMR) measurements by Murty et al 23 on highly deformed aluminum foils have shown that strain rates on the order of 10 À4 s À1 can generate even higher excess vacancy concentrations at room temperature (X V ¼ 10 À5 ). Geißler, however, estimated the strain rates during the bonding process to be 10 s À1 to 30 s À1 .…”
Section: Discussionmentioning
confidence: 99%
“…where  is a structural parameter describing the distribution of dislocations which depends on temperature, and the value can be fitted as 0.75exp(0.0039T) at a temperature above 700°C [14];  is the shear modulus;  0 is the atomic volume; A and n are empirical constants; D v is the diffusion coefficient of vacancies; Q def is the apparent activation energy for deformation;  is a constant associated with the mechanical production of jogs; b is the Burgers vector; C j is the concentration of thermal jogs, given by exp(E j /kT) [12] where E j is the jog formation energy being calculated by 0.1b 3 [15];  is a parameter which describes the neutralization effect produced by the presence of vacancy emitting and vacancy absorbing jogs and may be calculated by 0.5-10C j if C j <0.05, and else  is equal to 0 [12].…”
Section: Theorymentioning
confidence: 99%